2011
DOI: 10.1590/s1516-35982011001000002
|View full text |Cite
|
Sign up to set email alerts
|

Sward canopy structure and performance of beef heifers under supplementation in Brachiaria brizantha cv. Marandu pastures maintained with three grazing intensities in a continuous stocking system

Abstract: -The objective of this study was to assess the sward canopy structure of Brachiaria brizantha cv. Marandu pastures maintained in three grazing intensities under continuous stocking system during the rainy season, along with the behavior and performance of grazing beef heifers supplemented with mineral salt or an energy/protein supplement. Three levels of forage allowance were assessed: 2.0, 2.5 and 3.0 kg of forage/kg of live weight, combined with two supplements (ad libitum mineral salt, and an energy/protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 9 publications
1
17
1
5
Order By: Relevance
“…The higher input of nitrogen in pasture has a direct effect on the forage mass and consequently the stocking rate (Moreira et al, 2014). The targets of grazing management with lower forage allowance imply an increase in the stocking rate by greater forage utilization (Casagrande et al, 2011). In the present study, as similar forage allowances were observed (3.2 and 3.4% BW/day of forage mass, respectively, in the mixed pasture and monoculture; data not shown), variations in stocking rate were due to forage mass.…”
Section: Discussionmentioning
confidence: 99%
“…The higher input of nitrogen in pasture has a direct effect on the forage mass and consequently the stocking rate (Moreira et al, 2014). The targets of grazing management with lower forage allowance imply an increase in the stocking rate by greater forage utilization (Casagrande et al, 2011). In the present study, as similar forage allowances were observed (3.2 and 3.4% BW/day of forage mass, respectively, in the mixed pasture and monoculture; data not shown), variations in stocking rate were due to forage mass.…”
Section: Discussionmentioning
confidence: 99%
“…En un estudio realizado por Machado et al (2007), encontraron que la altura de la pradera de pasto Insurgente tuvo una relación lineal con la oferta de forraje. Para este mismo cultivar, se reportó que conforme se aumentó la asignación de forraje se incrementó la altura de la pradera hasta un punto donde se mantiene estable (Mesquita et al, 2010;Casagrande et al, 2011).…”
Section: Altura De Plantaunclassified
“…The pasture intensity to be chosen will depend mainly on the objective of the farmer as regards animal performance. In situations of higher pasture intensity, performance per area is prioritized; in low-intensity cases, the priority becomes individual performance (Casagrande et al, 2011a). This flexibility is possible because forage grasses can be managed in a wide range of grazing intensities without causing degradation of the pasture.…”
Section: Introductionmentioning
confidence: 99%